2018
DOI: 10.1002/ldr.3146
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of event‐based rainfall erosivity from radar after wildfire

Abstract: Rainfall erosivity impacts all stages of hillslope erosion processes and is an important factor (the ‘R factor’) in the Revised Universal Soil Loss Equation. It is estimated as the average annual value of the sum of all erosive events (EI30) over a period of many years. For each storm event, the EI30 value is the product of storm energy, E in MJ ha−1, and peak 30‐min rainfall intensity (I30, mm hr−1). Previous studies often focused on estimation of the R factor for prediction of mean annual or long‐term soil l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
0
12
0
1
Order By: Relevance
“…() have revealed that rainfall erosivity is the most important parameter that has the direct effect of climate change on water erosion. More importantly, hillslope erosion occurs mostly during a few severe storm or extreme events (Zhu et al ., ). Large and erosive storms are even more variable than annual rainfall totals.…”
Section: Discussionmentioning
confidence: 97%
“…() have revealed that rainfall erosivity is the most important parameter that has the direct effect of climate change on water erosion. More importantly, hillslope erosion occurs mostly during a few severe storm or extreme events (Zhu et al ., ). Large and erosive storms are even more variable than annual rainfall totals.…”
Section: Discussionmentioning
confidence: 97%
“…These main components were supported and supplemented with: a burn severity map (Storey, ); rainfall and erosivity calculations of the 1 February 2013 storm (Zhu et al., ); Light Detection and Ranging (LiDAR) data of the fire ground and a 1 m digital elevation model (DEM); and soil mapping for spatial extrapolation of site data.…”
Section: Methodsmentioning
confidence: 99%
“…• Understanding impacts on soil organic carbon (SOC) and nitrogen (N), • measurement and modelling soil erosion and groundcover recovery, and • understanding fluvial geomorphic and bedload change. These main components were supported and supplemented with: a burn severity map (Storey, 2014 ); rainfall and erosivity calculations of the 1 February 2013 storm (Zhu et al, 2018 ); Light Detection and Ranging (LiDAR) data of the fire ground and a 1 m digital elevation model (DEM); and soil mapping for spatial extrapolation of site data. Impacts on Soil organic carbon (SOC) was selected by NPWS as a proxy for understanding changes to soil structure and its relationship to soil stability and erosion and recovery of vegetation.…”
Section: Post Fire Assessments and Proposalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perbandingan antara data radar cuaca yang telah di kalibrasi dengan 12 penakar hujan tipping bucket untuk melakukan estimasi kejadian erosi. Hasil penelitian ini menunjukkan data radar cuaca dapat digunakan untuk menunjukkan waktu kejadian erosi dan sebagai informasi manajemen kejadian kebakaran hutan dan pengaturan tindakan terhadap erosi [22].…”
Section: Pendahuluanunclassified